PROSPECTS FOR DEVELOPING THE SMART FARMING CONCEPT TO DEAL WITH RURAL-URBAN TRANSFORMATION IN MEKARMUKTI VILLAGE, CIHAMPELAS SUB-DISTRICT, WEST BANDUNG DISTRICT - Rosanti Budimansyah, Camilla
The rapid growth of cities compared to their surrounding areas has triggered ruralurban transformation in the suburban villages of metropolitan areas. This often puts pressure on villages, especially those unprepared for such changes. Mekarmukti Village in Cihampelas Subdistrict, West Bandung Regency, located on the outskirts of Metropolitan Bandung, has experienced the impact of this ruralurban transformation. This can be seen from the introduction of technology in various life sectors, economic diversification, and the conversion of agricultural land into built-up areas. On the other hand, the agricultural potential in this village remains substantial and important to maintain, even enhance, to sustain its function as a food supplier. Given the potential and pressures present in Mekarmukti Village, developing the smart village concept, especially the smart farming dimension, can be an innovative approach to managing the agricultural sector. This study aims to explore the prospects of implementing the smart farming concept and to formulate strategies for its effective application in Mekarmukti Village. This prescriptive research employs the Rapid Rural Appraisal (RRA) approach. Data collection was carried out through interviews, observations, and literature studies, which were then analyzed using gap analysis and scenario planning methods. The study found that the smart farming concept has promising prospects for application in Mekarmukti Village's agricultural management. Some simple technologies are already in use. However, there is still a significant need for improvements in the provision of smart technology, farmers' capacity to use technology, and the management of agricultural institutions in managing agriculture. Therefore, the main strategies formulated include providing smart technology-based agricultural infrastructure and equipment, enhancing farmers' capacities, and optimizing the role of agricultural institutions.